Motivating Filipino Generation Z Employees at Work: Enablers and Outcomes - Talamayan, Mikee C (Archīum Ateneo, 2024)
Purpose This research focused on exploring factors that engender the work motivation of Gen Z employees and determined whether these factors affected their job satisfaction, engagement and affective commitment to their organizations. Design/methodology/approach The study employed a sequential mixed-methods approach, starting with 40 qualitative interviews to determine the work motivation factors of Gen Z employees. Findings of the qualitative study were then validated through an online survey that gathered data from 132 Gen Z employees. The quantitative study tested a model that relates factors that contribute to the motivation of Gen Z and positive employee outcomes – affective commitment, job satisfaction and work engagement. Findings Several factors were found as contributors to the work motivation of Gen Z employees: learning and development, family, impact on others and society, passion and enjoyment, financial security, ability to provide for oneself, personal achievement and self-rewards. The result of the structural equation modeling showed that the presence of motivating factors at work is a significant predictor of the outcome variables. Moreover, affective commitment was also found to partially mediate the relationship between the motivating factors and outcome variables – job satisfaction and work engagement. Originality/value This study addresses the dearth of empirical studies on factors that motivate Gen Z employees (the youngest employee cohort that recently joined the workforce) and how these contribute to positive work outcomes. Findings may help organizations curate their human resources management programs to attract, engage and motivate their Gen Z employees.